The discovery laboratory part II: A framework for incubating independent learning - Shah,UV; Chen,W; Inguva,K; Chadha,D; Brechtelsbauer,C (Education for Chemical Engineers, 2020)
We have conceptualized the Discovery Laboratory at Imperial College London into an educational framework that enables independent learning among students. The study demonstrates an effective implementation of the framework with associated benefits for the learner in the areas of cognitive skills (creativity and critical thinking), metacognitive skills (ability to reflect on the entire learning process) and affective skills (adaptive motivation). Key supportive elements were transferring ownership of the learning process to students and incorporating assessment criteria that reward creativity. The framework can be easily adapted to other experiential learning contexts.